Academic Achievement Constraints among General Secondary Students as Perceived by Passed and Non- Passed Students, and Their Parents - Rababeh, Hamzah (Jordan Journal of Educational Sciences, 2015)
This study aimed at identifying the constraints related to academic achievement among general secondary students as perceived by passed and non- passed students, and their parents in Irbid governorate during the academic year 2014/2015, and whether there would be statistical differences due to the variables of: student’s gender, place of residence and study stream. The study aims to investigate the low achievement of high school students in the national exam from social and national prespective. To achieve the aims of the study, a constraints academic achievement scale was developed consisting of (36) items distributed on three domains (self, instructional, and social domain). The sample of the study consisted of (1022) students and parents, represented (511) male and female students and (511) parents. The results revealed that there was a moderate level of constraints related to academic achievement among passed students compared to the non- passed who showed high level of constraints. it also revealed that there were no statistical significant differences among passed students in the level of constraints in all domains due to all study variables, and there were statistical significant differences in self and instructional domain due to the study stream in favor of information management students. With regard to non- passed students, there were no statistical significant differences in the level of constraints on the scale as a whole and all variables due to study variables. It was also found a moderate level of constraints related to academic achievement in the level of constraints among passed students’ parents, and high level of constraints among non-passed students’ parents, and there were no statistical significant differences on the scale as a whole and all domains in the level of their constraints due to gender variable